LIFE-SKILL PEMANFAATAN PEKARANGAN DENGAN HIDROPONIK PADA SISWA-SISWA MADRASAH ALIYAH MADANIA BANTUL - Heti Herastuti; Tuti Setyaningrum; Ali Hasyim Al Rosyid (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Hydroponics is the cultivation of plants using water or without the use of soil. Hydroponics is one of the limited land acquisitions. Hydroponics development can be done at Madrasah Aliyah Madania Bantul, but it requires special skills for students who take extracurricular agriculture and livestock. The problem is limited land at the location of Madrasah Aliyah Madania Bantul. Land has not been utilized, hydroponic cultivation has not been implemented to the fullest, and students' knowledge and skills are still limited about hydroponics. The methods used are lectures, discussions, training, practice and mentoring. The implementation of activities at the location of Madrasah Aliyah Madania Bantul school at Pondok Pesantren Modern Yatim and Dhuafa Madania Jl Gedongkuning Gang Nakula No. 165 Banguntapan Bantul. The activity began in June 2021, the number of participants was 15 people. The result of community service that madrasah madania bantul students already have life skills about hydroponics indicated by results before and after training improved. Utilization of the yard in Madrasah Aliyah Madania Bantul already uses hydroponics with various models of hydroponic systems and it has produced hydroponic products.